An Efficient All‐Plastic Organic Waveguide Solid‐State Laser Devices with Distributed Bragg Reflector. Issue 1 (6th December 2017) - Tsutsumi, Naoto; Yamazaki, Ryo
Abstract : Organic dye or polymer waveguide laser is a promising next‐generation solid‐state laser device, because they are not only easily and inexpensively fabricated as laser sources, but also have high potential for bio‐sensing for hazardous materials and environments. The active layer and the effective resonator consist of all‐organic materials, which can be processed by solution‐casting or spin‐coating. Here, laser performances of all‐plastic organic waveguide solid‐state laser devices are reported with Bragg mirror and micro‐cavity, both being fabricated by the relief gratings. Waveguide consists of a high quantum yield organic dye of pyrromethene 567 as a lasing emitter and a cellulose acetate (CA) film as a waveguide matrix. The distributed Bragg reflector (DBR) region and the distributed feedback (DFB) resonator as a micro‐cavity are fabricated in the waveguide devices using a negative photoresist SU‐8 by an interference technique. The performances of lasing threshold and slope efficiency for both organic waveguide devices with DBR region and DFB resonator are evaluated. The slope efficiency of 2.01% and the lasing threshold of 45 µJ cm −2 are measured for the waveguide device with DBR region, whereas the waveguide device with DFB resonator gives the slope efficiency of 0.72% and the lasing threshold of 140 µJ cm −2 . Abstract : All‐plastic distributed Bragg reflector (DBR) organic waveguide laser device is reported. High quantum yield organic dye of PM567 is used as laser emitter, which is dispersed in CA waveguide film. DBR is fabricated by a negative photoresist SU‐8. Waveguide laser device with DBR region gives lower lasing threshold of 45 μJ cm −2 and higher slope efficiency of 2.01%.